Watch and Learn: Enhancing the Performance in Mathematics of Grade 3 Pupils through the use of Video-Based Instructional Material - Repolito, Mary Roselene M. (Future Science / FSH-PH Publications, 2025)
Mathematics is a foundational subject, yet many elementary pupils struggle with abstract concepts such as multiplication and division. In the Philippines, gaps in mathematical proficiency remain evident in national and international assessments, further aggravated by limited instructional support and inadequate learning resources. Video-based instructional materials offer a promising approach by integrating visual, auditory, and contextual elements to make mathematics more interactive and accessible. This study employed a one-group pretest–posttest design with 38 Grade 3 pupils from Tinigaw Elementary School during S.Y. 2023–2024. A validated researcher-made test (KR-20 = 0.822) identified least mastered competencies and measured learning gains, while semi-structured interviews explored pupils’ challenges. Experts evaluated the acceptability of the developed materials using the DepEd LRMDS tool. Pretest results showed low mastery in the properties of multiplication (42%) and multi-digit division problems (62%). Qualitative findings revealed that pupils struggled with weak foundational knowledge, limited guidance, and poor-quality modules. Difficulties in multiplication and division, especially in problem-solving, and mismatched examples contributed to frustration and incomplete activities. After 12 weeks of video-based lessons, pupils’ mean performance improved significantly from 5.16 (SD = 2.03) to 8.61 (SD = 1.17), with a paired-sample t-test confirming statistical significance (t = -10.795, p < .05). Expert evaluation rated the materials “Acceptable” (M = 1.99). These results suggest that video-based instructional materials effectively enhance mathematical performance, increase engagement, and address learning gaps, supporting their integration in basic education to improve achievement in Mathematics.